Adult Caregivers in the United States: Characteristics and Differences in Well-being, by Caregiver Age and Caregiving Status - Lynda A. Anderson, PhD; Valerie J. Edwards, PhD; William S. Pearson, PhD; Ronda C. Talley, PhD, MPH; Lisa C. McGuire, PhD; Elena M. Andresen, PhD (Centers for Disease Control and Prevention, 2013)
We examined the characteristics of adults providing regular care or assistance to friends or family members who have health problems, long-term illnesses, or disabilities (ie, caregivers). We used data from the 2009 Behavioral Risk Factor Surveillance System (BRFSS) to examine caregiver characteristics, by age and caregiving status, and compare these characteristics with those of noncaregivers. Approximately 24.7% (95% confidence interval, 24.4%-25.0%) of respondents were caregivers. Compared with younger caregivers, older caregivers reported more fair or poor health and physical distress but more satisfaction with life and lower mental distress. Understanding the characteristics of caregivers can help enhance strategies that support their role in providing long-term care.